COMPANY ACCOUNTS IN BRITAIN: THE JENKINS REPORT. - Edey, Harold C. (The Accounting Review, 1963)
Abstract One hundred years ago the Parliament of the Great Britain enacted the Companies Act of 1862. This Act was to be, for nearly half a century, the main statute for the regulation of British companies; and in the Act's provisions, or in what was lacking in those provisions, the strong individualism and laissez-faire spirit of latter 19th century Great Britain were manifest. For the Act contained no mandatory provisions with respect to accounts or audit: these were matters of private contract, to be left to the stockholders. Major reforms related to company Act took place in Great Britain. In the year 1962, Jenkins Report was presented. Much of the Report is concerned with the general law. Generally, the accounting recommendations of this Report can be regarded as an attempt to add marginal improvements to existing legislation, rather than as a plan of radical change. Many of the improvements will be valuable. The general impression that the Report gives is of a Committee that, as a whole, possessed a high technical competence in law and accounting, but a substantially lower one in economic policy.